Are HFpEF and HFmrEF So Different? The Need to Understand Distinct Phenotypes - Palazzuoli, Alberto; Beltrami, Matteo (Frontiers in Cardiovascular Medicine, 2021)
Traditionally patients with Heart failure (HF) have been divided according to ejection fraction (EF) threshold more or less than 50%. In 2016 the ESC Guidelines introduced a new subgroup of HF patients including those subjects with EF ranging between 40-49% called Heart failure with mid-range EF ( HFmEF). This group is poorly represented in clinical trials and it includes both patients with previous HFrEF having a good response to the therapy as well as subjects with initial preserved EF appearance in which systolic function became to be impaired. The categorization according to EF has recently questioned because this variable is not really representative of the myocardial contractile function and it could vary in relation to different hamodynamic conditions. Therefore, EF could significantly change over the short term period and its measurement depends on the scan timing course. Finally, although EF is widely recognized and measured in all the world, it has significant inter observer variability even in most accredited echo laboratories. These assumptions imply that the same patient evaluated in different period or by different physicians could be classified as HFmEF or HFpEF. Thus, the two HF subtypes probably subtend different response to the underlying pathophysiological mechanisms. Similarly, the adaptation to hemodynamic stimuli and to metabolic alterations could be different for different HF stages and period. In this review we analyse similarities and dissimilarities and we hypothesize that clinical and morphological characteristics of the two syndromes are not so discordant.